"Regionalism, multilateralism, and economic integration" - "Sampson, Gary P.( ed.)" (New Delhi, 2004)
In recent years, the central question relating to regional trade agreements has been whether or not they have promoted deeper integration in the regulatory structures of the participating countries. The answer has profound implications for the future of multilateral cooperation through the World Trade Organization (WTO) and international economic relations in general. This volume examines a number of different regional agreements and finds that there is no one model for what constitutes deeper integration. The authors conclude that regional trade agreements have led to deeper integration in a number of fields, and that the regional processes and rules have been consistent with the multilateral obligations of the countries involved. They find that recent agreements are generally more effective in facilitating trade and improving transparency than the more remote WTO procedures.
Keywords: Regionalism